Width and neurophysiologic properties of tissue bridges predict recovery after cervical injury. (11th June 2019) - Vallotton, Kevin; Huber, Eveline; Sutter, Reto; Curt, Armin; Hupp, Markus; Freund, Patrick
Abstract : Objective: To assess whether preserved dorsal and ventral midsagittal tissue bridges after traumatic cervical spinal cord injury (SCI) encode tract-specific electrophysiologic properties and are predictive of appropriate recovery. Methods: In this longitudinal study, we retrospectively assessed MRI scans at 1 month after SCI that provided data on width and location (dorsal vs ventral) of midsagittal tissue bridges in 28 tetraplegic patients. Regression analysis assessed associations between midsagittal tissue bridges and motor- and sensory-specific electrophysiologic recordings and appropriate outcome measures at 12 months after SCI. Results: Greater width of dorsal midsagittal tissue bridges at 1 month after SCI identified patients who were classified as being sensory incomplete at 12 months after SCI ( p = 0.025), had shorter sensory evoked potential (SEP) latencies ( r = −0.57, p = 0.016), and had greater SEP amplitudes ( r = 0.61, p = 0.001). Greater width of dorsal tissue bridges predicted better light-touch score at 12 months ( r = 0.40, p = 0.045) independently of baseline clinical score and ventral tissue bridges. Greater width of ventral midsagittal tissue bridges at 1 month identified patients who were classified as being motor incomplete at 12 months ( p = 0.002), revealed shorter motor evoked potential (MEP) latencies (r = −0.54, p = 0.044), and had greater ratios of MEP amplitude to compound muscle action potential amplitude ( r = 0.56, p = 0.005). Greater width of ventral tissue bridges predicted better lower extremity motor scores at 12 months ( r = 0.41, p = 0.035) independently of baseline clinical score and dorsal tissue bridges. Conclusion: Midsagittal tissue bridges, detectable early after SCI, underwrite tract-specific electrophysiologic communication and are predictors of appropriate sensorimotor recovery. Neuroimaging biomarkers of midsagittal tissue bridges may be integrated into the diagnostic workup, prediction of recovery, and patients' stratification in clinical trials.